Parsivel disdrometer measurements at the coast of Andøya, Norway during March 2021 - Harald Sodemann; Andrew Walter Seidl; Iris Thurnherr; Alena Dekhtyareva (PANGAEA, 2025)
During a 2-week measurement campaign from 15-31 March 2021 (ISLAS2021), we collected a comprehensive dataset characterizing the atmospheric water vapour and precipitation stable isotope and aerosol composition at a coastal station in the European sub-Arctic. Located at the northeastern coast of the Nordic Seas, stable water isotope measurements with cavity ring-down spectrometers (CRDS) were collected at Andenes, Norway close to sea level and at the nearby ALOMAR mountain top observatory at 370 m a.s.l. Paired water vapour isotope and precipitation measurements at sub-event time resolution were collected at both station locations. These were supplemented with water vapour isotope measurements at the cities of Tromsø, Norway and Bergen, Norway. Surface precipitation samples were collected on a per-event basis along a transect towards the south to assess spatial representativeness. Measurements of ice nucleating particle concentrations were taken at sea level during precipitation events, supplemented by continuous size-resolved aerosol measurements. These detailed measurements were complemented by additional instrumentation to characterize the atmospheric conditions, including ground-based vertical-pointing rain radars, disdrometer, frequent radiosonde ascents and a ceilometer. All stable water isotope measurements have been calibrated onto the VSMOW-SLAP scale. During the campaign, weather conditions were alternating rapidly between warm mid-latitude air masses and marine cold-air outbreak conditions. The data from the ISLAS2021 measurement campaign therefore provide insight into a variety of mixed-phase precipitation processes, atmospheric long-range transport, and the dynamics of high-latitude weather system with the combined perspective of stable water isotopes and aerosol measurements. This dataset contains measurements of precipitation amount, visibility, weather code, particle fall speed distribution, and precipitation size distribution for the site Coast near Andenes, Norway, during the ISLAS2021 field campaign. Distribution of particle size and particle speed were classified into 32 range bins. The primary purpose of this dataset is to report precipitation characteristics at high time resolution. Measurements were obtained from an OTT Parsivel 2 disdrometer was installed near the shoreline at the base of the north-facing slope of Andhauet mountain. All variables are available at 60s time resolution.
In: Sodemann, Harald; Seidl, Andrew Walter; Thurnherr, Iris; Dekhtyareva, Alena; David, Robert Oscar; Carlsen, Tim; Chandler, David M; Schäfer, Britta; Gjelsvik, Astrid Bragstad; Touzeau, Alexandra; Zannoni, Daniele; Baumgartner, Gerd; Storelvmo, Trude; Wieder, Jörg; Kanji, Zamin A; Flügge, Martin (2025): ISLAS2021: Calibrated stable water isotope measurements and aerosol measurements at the coast of northern Norway during March 2021 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984616